1972
DOI: 10.1063/1.1678800
|View full text |Cite
|
Sign up to set email alerts
|

Charge Distribution of the Azide Ion

Abstract: Vibrational relaxation of azide ion in water: The role of intramolecular charge fluctuation and solventinduced vibrational coupling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Therefore, it is natural to invoke the nearby Thr-199 as the group that modifies the potential-energy function and controls the charges of Zn-bound azide. The charge on N (2) in isolated azide is Ϸϩ1 electron (e), whereas the end atoms each have a ϷϪ1 e charge (33). Recent calculations (34) have shown that the Zn-bound azide N (2) becomes more positive by 0.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is natural to invoke the nearby Thr-199 as the group that modifies the potential-energy function and controls the charges of Zn-bound azide. The charge on N (2) in isolated azide is Ϸϩ1 electron (e), whereas the end atoms each have a ϷϪ1 e charge (33). Recent calculations (34) have shown that the Zn-bound azide N (2) becomes more positive by 0.…”
Section: Discussionmentioning
confidence: 99%
“…However, NaN3 is not already a purely ionic compound since the valence states are hybridized with the cation states in the range of 40,lx,30,, the maximum hybridization occurring in 4ag. This results in the reconstruction of the isolated N; spectrum [19] and in lowering the 4ag band energy with respect to lxu. It should be noted that similar data were also obtained for LiN3 [S] where one notes that lithium azide is not a purely ionic compound.…”
Section: Band Structuresmentioning
confidence: 99%
“…As a classical example of a strong nucleophile, the azide anion is of considerable importance in organic and inorganic chemistry. The structure and properties of N 3 - have been well studied by various spectroscopic methods in the gas phase, solution, and crystal and solid matrixes. Theoretical calculations have also been carried out on the electronic structure of the azide anion and its behavior in solution. Despite all the experimental and theoretical investigations in bulk solution, little information has been obtained about the microsolvation of the azide anion in water clusters, which can provide molecular level understanding about the azide-water interactions. The large values of the quadruple moment and polarizability 22 make N 3 - a very special solute.…”
Section: Introductionmentioning
confidence: 99%